Suggesting a Mathematical Model for the Mechanism of Action of the Selective Wavelength-Switch WSS Based on MEMS Micro-Electromechanical Mirrors System to Improve the Performance of Flexible Optical Networks - الرضوان, هيثم; عيسى, هديل; خضور, اصالة (Latakia University Journal -Engineering Sciences Series, 2022)
The use of the Internet and social networking applications required raising the efficiency of the network and increasing the capacity. The main orientation was the optical networks that form the physical basis of the World Wide Web. Conventional optical networks suffer from limited bandwidth of the optical spectrum, in addition to increased energy consumption and increased cost of optical equipment. Therefore, these networks were developed to be able to select the bandwidth flexibly; It allowed the spectrum to be divided into a group of frequency slots with a width of 12.5 GHz, and thus we obtained variable bandwidth and fast access very effectively, so these networks are called flexible optical networks. New research has focused on the development of flexible optical networks, either through the control plane or through the physical layer. In our research, we focused on improving the performance of these networks by developing optical nodes within the physical layer; The physical layer has a dynamic response to the variable bandwidth requirements of the host layer. Our study is based on proposing a mathematical model of the Wavelength Selective Switch (WSS) based on Micro-Electromechanical Mirrors System (MEMS) to get the best yield and the best selectivity by selecting the appropriate photonic elements.